Meningkatkan Kemampuan Merias Wajah Melalui Multi Methode Bagi Penyandang Low Vision (Single Subject Research di Kampus PLB FIP UNP) - Suci Ramadini (Universitas Negeri Padang, 2014)
Abstract : This research was conducted due to the prpblems found in Special Needs Education department indicating that students with Low Vision the fourth semester got difficulties to apply makeup appropriately. Bades on the result of the research, it was revealed that the ability of the students with low vision to apply makeup improved after Multi Methode applied. In the baseline condition (A) which consisted of seven meetings, the students score was 53%. In the intervention condition (B) that consisted of eleven meetings, the student ability to apply makeup improved from the eleventh meeting to the eighteenth meeting in which their score was 100%. From trhe result of data analysis, it was figured out that there was a changing on the tendency of direction which improved (+) from baseline condition to the intervention one. The persentage of the data overlapped was smll (54,5%) signifying that the use of Multi Methode gave better effect on the ability of the students with low vision to apply makeup. This result had shown that the use of Multi Methode could improve the ability of the studnets with low vision to apply makeup at campus of PLB FIP UNP. Kata Kunci : Penyandang Low Vision, Multi Methode, Kemampuan Merias Wajah